Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Hemat Laundry Tanjung Pura - Audri Pratiwi; Suri Amilia; Rahmi Meutia (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of service quality, price, simultaneously on customer satisfaction at Tanjung Pura Laundry Savings. The sample used in this study amounted to 96 respondents. The data analysis method used multiple linear regression analysis, t test, F test, and coefficient of determination test. The regression equation in this study is Y = 3,820 + 0,115X1 + 0,190X2. Service quality has a significant effect on customer satisfaction at Tanjung Pura Laundry Savings, where from the t test results, the t sig value is satisfaction at Tanjung Pura Laundry, where the t test results obtained the t sig value. and location simultaneously have a satisfaction at Tanjung Pura Laundry Savings, where from the F test the F value of sig is obtained. 0.000 < 0.05. From the coefficient of determination test it can be explained that service quality, price, affect customer satisfaction at Tanjung Pura Laundry Savings by 59,4%, while the remaining 40,6% is influenced by other variables outside this research model.